2001
DOI: 10.1002/hrdq.15
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between organizational support, employee development, and organizational commitment: An empirical study

Abstract: An empirical study conducted in a major midwestern hospital found that organizational commitment and perceived organizational support were significantly correlated with satisfaction with career development. Results suggested that when organizations make efforts to develop their managers, the managers become more committed to the organization and also more likely to develop their employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
156
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(183 citation statements)
references
References 26 publications
15
156
0
4
Order By: Relevance
“…According to another result there was a significantly positive relationship between perceived organizational support and affective commitment and H 3 was accepted. That result supports the studies of Eisenberger et al (1990), Shore and Tetrick (1991), Shore and Wayne (1993), Tansky and Cohen (2001), Rhoades, Eisenberger and Armeli (2001). Finally, the hypothesis was tested whether there was a moderator role of perceived organizational support between the relationship interactional justice and affective commitment or not.…”
Section: Conclusion and Suggestionssupporting
confidence: 78%
“…According to another result there was a significantly positive relationship between perceived organizational support and affective commitment and H 3 was accepted. That result supports the studies of Eisenberger et al (1990), Shore and Tetrick (1991), Shore and Wayne (1993), Tansky and Cohen (2001), Rhoades, Eisenberger and Armeli (2001). Finally, the hypothesis was tested whether there was a moderator role of perceived organizational support between the relationship interactional justice and affective commitment or not.…”
Section: Conclusion and Suggestionssupporting
confidence: 78%
“…That is, the advocacy and involvement in developing empowerment initiatives can by viewed by union members as a form o f perceived union support (Shore et al, 1994). The consistent findings in the literature that perceived organizational support positively affects company commitment (e.g., Eisenberger et al, 2001;Hutchison, Sowa, Eisenberger, & Huntington, 1986;Rhoades, Eisenberger, & Armeli, 2001;Settoon, Bennett, & Liden, 1996;Tansky & Cohen, 2001) suggest that perceived union support should positively affect union loyalty. Consistent with this idea, Shore et al (1994) and Sinclair and Tetrick (1995) found perceived union support to be positively related to union loyalty.…”
Section: Employee Commitment To the Unionsupporting
confidence: 57%
“…It is also believed that employees may feel obliged when employers give some acknowledgement to their efforts by offering them proper benefits and opportunities to excel which subsequently leads to reciprocationa; of commitment in the organizations (Shore & Tetrick, 1991;Tansky & Cohen, 2001). Social exchange theory asserts that organizational commitment is expected to lower turnover intentions (Cropanzano & Mitchell, 2005).…”
Section: The Relationship Between Organizational Commitment and Turnovermentioning
confidence: 99%